2022
DOI: 10.1007/s00018-022-04549-y
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the human trophoblast stem cell state from pluripotent and somatic cells

Abstract: Trophoblasts are specialized epithelial cells that perform critical functions during blastocyst implantation and mediate maternal–fetal communication during pregnancy. However, our understanding of human trophoblast biology remains limited since access to first-trimester placental tissue is scarce, especially between the first and fourth weeks of development. Moreover, animal models inadequately recapitulate unique aspects of human placental physiology. In the mouse system, the isolation of self-renewing troph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…67 JEG-3, JAR, and BeWo cells lines originate from human choriocarcinoma and while they are often used to model invasion, migration, and syncytialization of the human placenta, these cells are unlikely to recapitulate the behavior of healthy tissue. The synthetic hydrogel 3D culture model described in this work can be applied to more physiologically relevant cells to study placental development and microenvironment, such as induced pluripotent stem cell-derived trophoblasts 29,68 and primary trophoblast stem cells. [69][70][71] Cell processes such as invasion, migration, and signaling rely heavily on dynamic protein expression, interactions with ECM, and integrin expression, and our data with JEG-3, JAR, and BeWo demonstrate that a 3D synthetic hydrogel can provide these necessary cues.…”
Section: Synthetic Hydrogel Adhesion Ligand Signals Have Limited Infl...mentioning
confidence: 99%
“…67 JEG-3, JAR, and BeWo cells lines originate from human choriocarcinoma and while they are often used to model invasion, migration, and syncytialization of the human placenta, these cells are unlikely to recapitulate the behavior of healthy tissue. The synthetic hydrogel 3D culture model described in this work can be applied to more physiologically relevant cells to study placental development and microenvironment, such as induced pluripotent stem cell-derived trophoblasts 29,68 and primary trophoblast stem cells. [69][70][71] Cell processes such as invasion, migration, and signaling rely heavily on dynamic protein expression, interactions with ECM, and integrin expression, and our data with JEG-3, JAR, and BeWo demonstrate that a 3D synthetic hydrogel can provide these necessary cues.…”
Section: Synthetic Hydrogel Adhesion Ligand Signals Have Limited Infl...mentioning
confidence: 99%
“…To overcome this problem, a study merged syncytiotrophoblasts’ cell layers on semi-permeable supports. These cell layers of syncytiotrophoblasts can act as a sufficient barrier concerning both low- and high-molecular-weight xenobiotic compounds [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…TEAD signaling is strongly implicated in the differentiation of hiPSC to the trophoblast lineage 41 ; and recently Dattani et al 42 showed that suppression of YAP/TEAD signaling was critical to the insulation of naive hiPSC from trophoblast differentiation. Though the capacity for conventional hiPSC to undergo trophoblast differentiation has been the subject of considerable controversy 41,43 , it is certainly possible that formative state cells, closer to the naïve-state, might be capable of entering this differentiation pathway, and that regulatory elements in RMN 3 are in some way primed for activation in naïve and formative state cells 44 . RNM 8 was strongly enriched for G 1 cell cycle-associated TFs (E2F Family, E2F2, E2F5, SP-E2F Complex) which is consistent with the fact that the formative state has a highly proliferative phenotype and an abbreviated G 1 phase 1,45 (Figure 3A-C).…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate the utility of annotating the ATAC-seq peaks in the RNMs (pluripotency state, chromatin state, and predicted TFBSs), we plotted a 2 MB interval on chromosome 4 surrounding SMAD1 , which is a transcription factor involved in early cell fate decisions during specification of trophoblast and amnion, and later, gastrulation 41,49,50 via regulation of bone morphogenic proteins (BMPs). We observed nine formative-state associated peaks and multiple peaks binding SMAD Family (SMAD2 and SMAD4) and SOX-LEF1 Complex (SOX2, SOX3, SOX4, LEF1) TFs (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation